Perinatal outcome of term pregnancies with borderline amniotic fluid index: a prospective case control study - Desai, Devika V.; Mishra, Nigamananda; Savani, Gayatri V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: It has been since antiquity that the importance of amniotic fluid and fetal growth with perinatal outcome is being documented. But the lacunae lies in studying the relationship between borderline amniotic fluid and perinatal outcome. The following study was undertaken to provide recent data that would help predict perinatal outcome in borderline AFI pregnancies. Methods: About 144 patients were considered in the study OPD/IPD patients in obstetrics and gynecology department in Bhabha Atomic Research Centre and Hospital, with about 72 cases with borderline amniotic fluid index (5-8 cm) and controls with amniotic fluid index ≥9-25 cm. Patients were selected and subjected to history taking, examination, ultrasound test with doppler studies and perinatal outcome documented over a period of one year. Results: The incidence of borderline AFI in my study was 16%. 58% were primigravidas. Meconium stained liquor was found in 18% cases compared to 7% controls. Low birth weight was found in 12.5% cases and 2.7% in controls. On applying statistical test analysis chi square test, it was found that borderline amniotic fluid index in relation to presence of meconium stained amniotic fluid and low birth weight, p value was found to be statistically significant (<0.05). Conclusions: Borderline amniotic fluid and perinatal outcome had significant relationship in terms of meconium stained liquor and birth weight while rest had no significance. Thus, borderline amniotic fluid patients require vigilant fetal surveillance.